Surface tension of blood - Hrncír, E; Rosina, J (Physiological research, 1997)
The surface tension of blood assessed in a group of 71 healthy subjects (24 men and 47 women) by the drop method at a temperature of 22 degrees C was 55.89 x 10(-3) N x m(-1), S.D.=3.57 x 10(-3) N x m(-1). It did not correlate with age or sex of the examined subjects nor with any of the following variables: red cell sedimentation rate, blood haemoglobin levels, number of erythrocytes, total serum cholesterol, total serum triacylglycerols, creatinine blood levels, ALT and AST activity. The surface tension of blood and other body fluids can play an important part not only in the genesis and development of decompression sickness but also in other processes in the organism.
Keywords: Surface Tension; Blood; Middle Aged; mužské pohlaví; ženské pohlaví; dospělí; Humans; Adult; Female; Male; Adolescent; povrchové napětí; lidé; krev; mladiství; lidé středního věku